The Price of a 15-Year Delay in Diagnosis of Sheehan's Syndrome. Issue 2 (1st April 2016) - Parikh, Rohan; Buch, Varun; Makwana, Mitesh; Buch, Harit N.
Abstract : We describe a case of a 48-year-old woman who presented with a 15-year history of recurrent episodes of hypoglycemia and hyponatremia leading to altered behavior and generalized seizures. She underwent full clinical assessment, endocrine tests, and a pituitary magnetic resonance scan that showed pananterior hypopituitarism secondary to postpartum pituitary necrosis (Sheehan's syndrome). She was commenced on appropriate hormone replacement therapy, which led to significant improvement in lethargy, anorexia, muscle weakness, and episodes of hypoglycemia. In addition to the alleviation of her physical symptoms, she experienced a significant improvement in her psychological well-being and reduction in hospital visits. This case illustrates the impact of delay in diagnosis of an easily treatable medical condition and its socioeconomic implications, especially for the population of a developing country like India.